FEATURES PATHOGENESIS AND TREATMENT OF PERIODONTAL DISEASE IN DOMESTIC CATS - Киричко, Б. П.; Звенігородська, Т. В. (Scientific Progress & Innovations, 2013)
Found that when periodontal disease detected increased ESR, glucose, and gamma-globulin, reducing the number of red blood cells and white blood cells in the blood. In oral fluid celebrated hyperproteinemia and hyperglycemia. The dependence of the level of catalase and malondialdehyde during treatment. The combination of conservative and surgical treatment of inflammatory periodontal diseases in cats and implants "Biomin" make a positive impact.